THE SOCIAL AND ECONOMIC IMPACT OF CRUISE TOURISM IN PUNTARENAS (COSTA RICA) - Mora Elizondo, María Lisbeth (2013)
This investigation took into account the Cruise Ship Tourism which arrives in Puntarenas City, season in which there is a lot of movement in the area and even it is shown more colorful and attractive. In this study, it will investigate about the social and economic impact generated precisely by the cruise ship tourism. Moreover, it was inquired into the activities which take place during the visit of the cruise ship, the action of the local government, as well as the presence of difficulties or needs to improve the tourism management in this sector and possible solutions according to the people involved.